Morphometry of seminiferous tubules of human testes in different age groups in Bangladeshi cadavers - Choudhury, S; Khalil, M; Chakraborty, K; Sultana, SZ; Manna, S; Rahman, MM; Ara, A; Haque, MA (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2012 Jan;21(1):34-38 The abstract of this article is available on the PubMed website